Devonian lacustrine shore zone architecture: Giving perspective to cliff exposures with ground penetrating radar. Issue 7 (29th August 2016) - Andrews, Steven D.; Moreau, Julien; Archer, Stuart
Abstract: Lake margin sedimentary systems have been the subject of only limited study. The cyclic Middle Devonian lacustrine succession of Northern Scotland contains repeated developments of shore zone sandstones and thus provides an ideal location for the study of these units. The cycles comprise deep lake, shallow lake, playa and shore zone facies. Detailed field observations are presented alongside ground penetrating radar data which has aided large‐scale and three‐dimensional characterization of the shore zone sand bodies. Loading and discrete channel forms are recognized in thin‐bedded sandstones within the lower portion of the lake shore zone successions. Up‐section, the sandstone beds appear to become amalgamated, forming subtle low angle accretionary bar complexes. Where imaged on the radar profiles, the repeated development of shoreward migrating features succeeded by more shallow angled lakeward accreting surfaces is recognized; these are ascribed to washover and swash–backwash processes, respectively. The orientation of these features is similar to palaeocurrent measurements from oscillation ripples, suggesting an alignment of the shore zone bars perpendicular to the prevailing wind direction. Further loaded sandstone beds and sand‐filled shallow channel features overlie the bar forms. The context of the shore zone facies allows the controls on its formation to be examined. The shore zone sandstones overlie playa facies which contain abundant desiccation horizons, reflecting the most arid phase in the climatically controlled lacustrine cycle. As climatic conditions ameliorated, the rejuvenation of fluvial systems resulted in the transport of sand out into the basin. Initial deposition was limited to intermittent events where sediment was laid down on a water‐saturated substrate. High resolution fluctuations in lake level resulted in periodic short‐lived reworking events along the lake margins which produced amalgamated sands, forming low relief bars. Shore zone reworking is likely to have occurred over a wide  area as the lake margin migrated back and forth, and gradually transgressed.